Adverse effects of amiodarone therapy in adults with congenital heart disease. (21st September 2018) - Moore, Benjamin M.; Cordina, Rachael L.; McGuire, Mark A.; Celermajer, David S.
Abstract: Objective: Amiodarone is a highly effective antiarrhythmic therapy, however its toxicity profile often limits treatment. This is particularly relevant in adults with congenital heart disease (CHD), who are often young and in whom other antiarrhythmic agents commonly fail or are contraindicated. We sought to determine incidence and predictors of adverse effects caused by amiodarone in adult CHD (ACHD). Design: A retrospective review of patients with moderate to complex ACHD treated with amiodarone at our center between 2000 and 2017 was performed. Incidence and predictors of adverse effects were described. Efficacy of amiodarone therapy in controlling the clinical arrhythmia was assessed as complete, partial, or failed. Results: Amiodarone was prescribed in 57 patients of 902 ACHD patients reviewed (6%), for a mean duration of 2.7 ± 4.3 years. Significant adverse effects occurred in 56%, most commonly thyroid dysfunction, with amiodarone‐induced thyrotoxicosis (AIT) in 30% and amiodarone‐induced hypothyroidism in 14%. AIT frequently led to arrhythmia exacerbation and occurred most in those with Fontan anatomy. Severe dermatological effects were seen in 7% and bradycardia requiring pacing in 5%. Interstitial lung disease, peripheral neuropathy and alopecia were observed in single cases. Amiodarone toxicity led to discontinuation of the drug in 42%. Amiodarone was highly effective when tolerated, however, achieving complete arrhythmia control in 63%, partial control in 35%, with failure to control in only one patient. Conclusions: Amiodarone therapy is effective in moderate to complex ACHD patients, but is frequently limited by adverse effects. ACHD patients seem especially vulnerable to thyroid dysfunction, with Fontan patients in particular at increased risk of AIT.